IDENTIFIKASI Fase KOMPOSIT OKSIDA BESI - ZEOLIT ALAM HASIL PROSES MILLING - Yosef Sarwanto; Grace Tj.S.; - Mujamilah (Widyariset, 2010)
Iron oxide – nature zeolite composite has been obtained by using milling process with varied milling time of 1.5 hours, 4.5 hours, 9 hours, and 13.5 hours. Weight ratio of iron oxide to nature zeolite was set to 1:1. The resultof milling process was identified using X-ray diffraction (XRD) technique, then compared the pattern to JCPDSICDD (Joint Committee on Powder Diffraction Standard - International Centre for Diffraction Data) data base.XRD pattern of the composite showed that α-Fe2O3 phase growth with increasing milling time from 1.5 hours to 13.5 hours milled as a result of Fe3O4 oxidizing. Visual observation was done to know the binding of iron oxide to nature zeolite by immersing the composite in water media and attracting with magnetic field.